2017
DOI: 10.1902/jop.2016.160529
|View full text |Cite
|
Sign up to set email alerts
|

Erbium, Chromium:Yttrium‐Scandium‐Gallium‐Garnet Laser Effectively Ablates Single‐Species Biofilms on Titanium Disks Without Detectable Surface Damage

Abstract: The Er,Cr:YSGG laser with radial firing tip and water spray was able to effectively ablate ≥95% of biofilm on all types of tested titanium surfaces, using clinically relevant power settings, without causing measurable physical changes to surfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 25 publications
4
10
0
Order By: Relevance
“…Similar results were observed when using the Er,Cr:YSGG laser for P. gingivalis ablation, causing a 95% removal of biofilm without altering the surface roughness or changing the surface temperature of titanium discs [18].…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Similar results were observed when using the Er,Cr:YSGG laser for P. gingivalis ablation, causing a 95% removal of biofilm without altering the surface roughness or changing the surface temperature of titanium discs [18].…”
Section: Discussionsupporting
confidence: 68%
“…In contrast to previous studies [18,19,24,39] that used Ti discs, we used commercially available implants to closely simulate the clinical situations regarding the complex implant topography. Strever et al showed that a bacterial biofilm on a Ti disc was easily removed even by water spray [18]. In this study, the surface roughness was not changed in any of the study groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no consensus in literature on the best protocol to decontaminate implant surfaces [21]. Decontamination with different solutions was unable to completely decontaminate implant surfaces [22,23] and could induce changes in the chemical and physical properties of implant surfaces [24], with partial reosseointegration being reported in animals [22].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that, regardless of implant surface alteration, using erbium, chromium-doped yttrium scandium gallium garnet (Er,Cr:YSGG) laser can lead to antibacterial properties of the implant surface. [18][19][20] However, surface defects on implant surfaces using Er,Cr:YSGG laser were reported. 21 A. actinomycetemcomitans and E. corrodens were selected due to their role in inflammation around the implant and also periodontitis.…”
Section: Introductionmentioning
confidence: 99%